Домик тетушки лжи: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2002)
Экземпляры: Ф.13 (20190912) / Инвентарный номер: 47160 / Цена: / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17.82 / ББК: 84(2Рос-Рус)6